Synthesis and biological evaluation of novel pyrrolo[2,1- c][1,4]benzodiazepine prodrugs for use in antibody-directed enzyme prodrug therapy - Masterson, Luke A.; Spanswick, Victoria J.; Hartley, John A.; Begent, Richard H.; Howard, Philip W.; Thurston, David E. (Bioorganic & medicinal chemistry letters, 2006)
Four novel pyrrolo[2,1- c][1,4]benzodiazepine prodrugs ( 1a, b and 2a, b) have been synthesized for potential use in carboxypeptidase G2 (CPG2)-based ADEPT therapy. The urea prodrugs ( 1b and 2b) are relatively unstable but the carbamate prodrugs ( 1a and 2a) are both stable in an aqueous environment and are good substrates for CPG2. The design, synthesis and evaluation of four novel pyrrolo[2,1- c][1,4]benzodiazepine (PBD) prodrugs ( 1a, b and 2a, b; Fig. 1) for potential use in carboxypeptidase G2 (CPG2)-based antibody-directed enzyme prodrug therapy (ADEPT) is reported. Although all four prodrugs were shown to be less cytotoxic than the released parent PBDs 3 and 4, the urea prodrugs 1b and 2b were found to be too unstable for use in ADEPT, whereas carbamates 1a and 2a are both stable in an aqueous environment and are good substrates for CPG2.